The Spread of SARS-CoV-2 Infection Among the Medical Oncology Staff of ASST Spedali Civili of Brescia: Efficacy of Preventive Measures - Dalla Volta, Alberto; Valcamonico, Francesca; Pedersini, Rebecca; Fornaro, Carla; Tovazzi, Valeria; Monteverdi, Sara; Baggi, Alice; Consoli, Francesca; Ferrari, Vittorio Domenico; Grisanti, Salvatore; Conti, Elisabetta; Amoroso, Vito; et al. (Frontiers in Oncology, 2020)
Patients with cancer are at higher risk of developing disease-related serious complications in case of contracting SARS-CoV-2. Oncology Units should implement all possible preventive measures to reduce the risk of viral transmission by healthcare professionals (HCPs) to patients. We conducted a surveillance for SARS-CoV-2 infection among staff members of the Medical Oncology Unit of ASST Spedali Civili in Brescia, one of the Italian areas most affected by the SARS-CoV-2 pandemic. The aim of this study was to demonstrate whether the recommended preventive measures, promptly implemented by the Unit, have been effective in reducing the virus spread among the HCPs. Between February 24th and May 19th SARS-CoV-2 infection was detected in 10 out of 76 HCPs healthy workers (13%). Six of them developed symptomatic disease leading to home quarantine and 4 remained asymptomatic and infection was revealed when serology test was performed on all staff members of the Unit. In the 7 HCPs, in which it was possible to trace the person to person infection, the contagion occurred as a result of not protected contacts or partially protected by surgical masks. In particular the 4 asymptomatic professionals did not stop working but a widespread outbreak in the Unit was avoided. Adherence to recommended preventive strategies, and in particular wearing of surgical masks by both the HCPs and the patients are effective in reducing and preventing the viral spread.